Screening of Antioxidant Effect of Spontaneous and Bioinoculated with Gluconobacter oxydans Fermented Papaya: A Comparative Study - Mariana Leitão; Beatriz Ferreira; Beatriz Guedes; Daniela Moreira; Pablo A. García; Luisa Barreiros; Patrícia Correia (Fermentation, 2023)
Fermented papaya is recognized as a nutraceutical with a diverse and rich composition. Fermentation of fruit with desirable microorganisms could be a strategy to improve the nutritional quality and profile of the fruit. Despite the popularity of fermented papaya, there is still a lack of knowledge on the effects of various fermentation parameters. The goal of this study was to screen the antioxidant and other properties of the products obtained through a variety of fermentation experiments, as well as the impact of adding Gluconobacter oxydans on their physicochemical properties. The strategies used to produce the fermented papaya extracts were spontaneous fermentation and bioinoculation with G. oxydans. Different fermentation tests were performed to measure pH, total soluble solids, reducing sugars, sodium pyruvate content, total phenolic content (TPC), and ferric reducing antioxidant power (FRAP). There was a decrease in TPC during spontaneous fermentations (five assays). However, it can be observed that in the fermentation assays with G. oxydans, there was an increase in TPC and antioxidant properties. The highest content of TPC was observed on the eighth day of P7 (260.18 ± 0.02 µg gallic acid equivalents mL−1) which was fermented with the bacteria and supplemented with glucose. Therefore, phenolic compounds in fermented papaya were found to increase antioxidant capacity as a result of bioinoculation with G. oxydans.